2017
DOI: 10.29063/ajrh2017/v21i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific Factors and Contraceptive Use: A Mixed Method Study among Women, Men and Health Providers in a Rural Ghanaian District

Abstract: Suitable options for improving women's access to effective, safe and context-specific contraceptive methods must be explored to curtail rising unmet needs for contraceptive use in rural Ghana. The study aimed to outline context-specific factors associated with contraceptive use, access on demand and future use intentions among women in one district of Ghana. Using mixed method approach, quantitative data (n=720) was collected among women aged 18-28. Focus group discussions and in-depth interviews were also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…For women perception of male enrolment in family planning they consider gender-equitable norms [14] and male partner support can increase the prevalence of modern contraceptive use [13]. This review also pointed some measures to increase use and communication of family planning among men.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For women perception of male enrolment in family planning they consider gender-equitable norms [14] and male partner support can increase the prevalence of modern contraceptive use [13]. This review also pointed some measures to increase use and communication of family planning among men.…”
Section: Discussionmentioning
confidence: 94%
“…Review articles show that law percentage of men involved in family planning practices [6]. From women perspectives men were seen as an obstacle and never enabled them to plan their next pregnancy [13]. Men engagement in family is affected by different factors [7] [8] [9] [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When couples negotiate reproductive outcomes, this is done against the backdrop of normative values, and if they disagree, whether this is real or perceived, there needs to be some form of conflict resolution [6]. As a result of the outcome of couple communication, or the absence of any communication, women may decide on their own to use a family planning method, even if this means using a method covertly [2,5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Such suspicions, and the tension they cause may lead to disclosure by some women, ultimately bringing about improvement in communication between partners [10]. On the other hand, it has been reported that if a male partner discovers on his own that a woman is using a method without his approval, he may feel betrayed [5,10] and could report her to her parents, accuse her of infidelity, stop having sex with her, start an extramarital affair, physically abuse her, marry another wife, withdraw economic support, or even divorce her, all in a bid to "punish" and "disgrace" her for her actions [5,[8][9][10]12,13].…”
Section: Introductionmentioning
confidence: 99%